Metamagnetism in nanosheets of Co-II-MOF with T-N at 26 K and a giant hysteretic effect at 5 K - Gupta, Kriti; Dadwal, Arun; Rana, Shammi; Jha, Plawan Kumar; Jain, Anil; Yusuf, S. M.; Joy, Pattayil A.; Ballav, Nirmalya (Inorganic Chemistry, 2018)
Herein, we have synthesized at room-temperature two-dimensional nanosheets of a MOF comprised of cobalt(II) ion with benzenedicarboxylic acid ligand, which exhibited unusual magnetic properties. Direct-current magnetic susceptibility revealed an anti-ferromagnetic (AFM) transition at 26 K (Neel temperature, T-N) followed by a canting of the spin moments along with the concomitant appearance of a sigmoidal-shaped magnetization versus field (M-H) curve at 15 K. Such a canted AFM ordering led to nonzero remnant magnetization with a remarkably high coercive field of similar to 10 kOe at 5 K. Metamagnetism was further: substantiated by the alternating-current magnetic susceptibility measurements.

Magnetic and magnetoelastic properties of Ni-substituted cobalt ferrite - Bhame, Shekhar D.; Shirolkar, Mandar M.; Joy, Pattayil A. (IEEE Magnetics Letters, 2021)
In this letter, magnetic and magnetostriction studies were performed on spinel ferrite Co1-xNixFe2O4 (CNF series) with 0.0 < x < 0.5. All the samples were synthesized by the conventional ceramic method and confirmed to be forming pure spinel phase. The unit cell parameter showed gradual decrease with increasing Ni content. A linear decrease in saturation magnetization (M-s) and coercivity (H-c) was observed with increasing Ni substitution, which could be attributed to reduced magneto-crystalline anisotropy. The room temperature magnetostriction studies revealed a slow decrease in maximum magnetostriction, and interestingly, for 20% reduction of cobalt concentration, i.e., for x = 0.2, a magnetostrictive strain of -164 ppm and substantially high stress sensitivity of -56 x 10(-6) A(-1) m were observed, making Co0.8Ni0.2Fe2O4 suitable for application as a magnetostrictive stress-sensing material.
Keywords: Ferrite; Magnetism in solids; Magnetostriction; oxide; stress sensing

Magnetostriction studies on transition metal substituted cobalt ferrite - Bhame, D. Shekhar; Bhapkar, Abhishek; Shirolkar, Mandar M.; Joy, Pattayil A. (Journal of the Indian Chemical Society, 2022)
Structural, magnetic and microstructural properties of transition metal (TM) substituted cobalt ferrite Co0.9TM0.1Fe2O4 (where TM = Ti, Cr, Mn, Ni and Cu and Zn) were investigated. The present study shows marked dependence of the magnetostriction on the concentration of the substituted transition metal ions for Cobalt in CoFe2O4. The magnetic characteristics of the prepared compositions such as coercivity, anisotropy constant and saturation magnetization changed significantly on transition metal substitution. The present study shows the way to tune the anisotropy of cobalt ferrite by effective substitution of other transition metal ions for Co which subsequently affects the stress sensing performance by changing the slope of the magnetostriction curve. Apart from the magnetic properties the microstructure can also be effectively modified by substitution of other transition metal ions. Only 10% substitution of cobalt showed drastic influence on magnetostriction and slope of magnetostriction curve. The composition with 10% nickel Co0.9Ni0.1Fe2O4 exhibited maximum slope for the magnetostriction curve of -53.7 ppm/Oe, along with reasonably high magnitude of strain of 186 ppm making it a suitable for exploring stress sensing applications.
Keywords: Ferrite; Magnetoelastic; Magnetostriction; oxide; stress sensing